Development of a prototype self-check system for the U.P. Diliman Main Library - Ong, Joseph Carl B.; Dorado, Dan Anthony D. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
Libraries often rely on technology to increase their efficiency and productivity especially on circulation process as this involves manual and repetitive tasks. Self-check systems are examples of technologies used in circulation but the products marketed by companies to libraries are more often expensive which makes libraries think if the benefits outweigh the costs. With the recent trend of open source software and librarians having IT skills, open source Self-Checkout systems have become available. In line with this, the author sought the development of a prototype self-check system for the U.P. Diliman Main Library while also finding whether the system usable and can increase the efficiency of the circulation process.
Using an existing open source self-checkout system as a foundation, the self-check system was developed primarily using PHP and communications via SIP2 protocol. System Usability Scale (SUS) was used to evaluate the system's usability while user evaluation was used for measuring the feature and design. Time-motion study was conducted to know if the system has the potential to be efficient.
It was found that the prototype self-check system was above average when compared to other products subjected to SUS evaluation. Overall, the users were satisfied with the functionality and design but were looking for improvements in the security feature, sounds and presentation of instruction. The time-motion study showed that the system has potential to be efficient but it is inconclusive if it is more efficient and productive to use than going through staffed circulation process.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Library circulation and loans -- Philippines -- Quezon City; Information retrieval -- Computer programs